Perancangan Dan Implementasi Robot Keseimbangan Beroda Dua Berbasis Mikrokontroler - Awal, Hasri; Hendrik, Billy; Arby, Willya (Jurnal Sains dan Teknologi (JSIT), 2022)
In today's modern world, there are many scientists and resources created and developed by people to facilitate their work. Be it in the field of Industry, Medical, to the world of Education. One example of scientists and renewal of sources. This can be proven by the many technologies in the field of robotics that are deliberately made to help human work. If humans have five senses such as eyes to see, then the robot can be in the form of sensors such as photodiodes, ultrasonic sensors to hear or even a camera to see and record. The purpose of this research is to design a reliable control system so that the robot can stand upright. To be able to balance the standing position of the robot with two wheels, a good and reliable control method is needed to maintain the robot's position perpendicular to the earth's surface without requiring external controllers and applying Self-balancing Control.